Risk factors for symptomatic venous thromboembolism in Thai hospitalised medical patients - Rojnuckarin, Ponlapat; Uaprasert, Noppacharn; Vajragupta, Laddawan; Numkarunarunrote, Numphung; Tanpowpong, Nathaporn; Sutcharitchan, Pranee (Thrombosis and Haemostasis, 2011)
Thromboprophylaxis for venous thromboembolism (VTE) failed to reduce overall mortality in hospitalised medical patients. As a VTE prediction model for Asians is still lacking, this study aimed to identify very high risk patients who would be the main target for prevention. In 2009, medical patients admitted to King Chulalongkorn Memorial hospital, a tertiary care centre, were prospectively evaluated for risk factors. The high-risk cohort was monitored for symptomatic VTE until six weeks after discharge. No heparin prophylaxis was given. Of 1,290 high-risk patients, 27 (2.1%, 95% confidence interval [CI] 1.3–2.9) developed proven VTE, 25.9% of which were diagnosed after discharge. Cases with VTE stayed longer in the hospital (median 18 vs. 11 days, p < 0.001). The significant risk factors in a multivariate analysis were autoimmune disease, solid tumours, family history of VTE, varicose vein and oestrogen with the relative risks of 11.8, 4.7, 120.3, 40.1 and 17.1 (p < 0.001, 0.001, 0.001, 0.002 and 0.038), respectively. Either autoimmune disease or solid tumours were found in 63% of VTE with the relative risk of 4.5 (95% CI 2.1–9.7, p < 0.001). In contrast, previously reported VTE scores in western patients could not stratify the VTE risks, but all the scores predicted higher mortality. In conclusion, VTE is common in Asian hospitalised medical patients. Patients with autoimmune disease and those with solid tumours are highly susceptible to VTE. A prophylactic strategy in these groups is required.
Keywords: Venous thromboembolism; medical patients; risk stratification